1999
DOI: 10.1111/j.1469-0691.1999.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Review on evaluations of currently available blood-culture systems

Abstract: m 3 Cl 7 m m -7 m 0-0 0 e C In < z 3 In c -. m 3 Q c 0 c ~ 3 m VI z C V m 3 -? (0 v) m 0, m U 3 a W W W

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 102 publications
1
5
0
Order By: Relevance
“…Indeed, it is commonplace to find that the caregivers can’t afford to pay for blood cultures before commencement of antibiotics. The use of manual culture techniques which accounted for 89% of techniques used in this review may have greatly hampered detection of GBS and other pathogens for the following reasons: automated blood culture systems support the growth of a wider range of organisms and at lower inoculum than manual systems, they also have antibiotic removal devices such as resins which help to enhance microbial growth in the presence of antibiotics, the continuous agitation of bottles by the equipment also encourages bacterial growth [ 55 , 56 ]. Dagnew et al reported higher isolation of GBS with automated systems[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is commonplace to find that the caregivers can’t afford to pay for blood cultures before commencement of antibiotics. The use of manual culture techniques which accounted for 89% of techniques used in this review may have greatly hampered detection of GBS and other pathogens for the following reasons: automated blood culture systems support the growth of a wider range of organisms and at lower inoculum than manual systems, they also have antibiotic removal devices such as resins which help to enhance microbial growth in the presence of antibiotics, the continuous agitation of bottles by the equipment also encourages bacterial growth [ 55 , 56 ]. Dagnew et al reported higher isolation of GBS with automated systems[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This contamination is mostly related to the sampling technique, since the possibility of contamination occurring in continuous automated systems is remote, although not nonexistent. 18,45,46 Rohner and Auckenthaler report a higher contamination rate of up to 4%, 36 while Bekeris et al reported a contamination rate of 2.89% for all cultures in a study conducted in 356 clinical laboratories. Of these, the rate of contamination in samples from neonates was 0.75% to 4.27%, with a median of 2.08%.…”
Section: Discussionmentioning
confidence: 97%
“…The culture media used were those recommended in the literature. 19,[35][36][37][38] The plates were incubated as recommended: for blood agar, in an Accurate Thermo Scientific or Felisa incubator at 37 8C with 5.5% CO 2 , and for MacConkey agar, Columbia agar, and potato dextrose agar, at 37 8C. We quantified the number of microorganisms on each culture plate in accordance with the Kass account, in colony-forming units (CFU) per milliliter.…”
Section: Methodsmentioning
confidence: 99%
“…During the visual inspection of bacterial growth, different parameters are assessed, such as the appearance of turbidity ("cloudiness") caused by undissolved particles in the broth, the deposition of bacterial colonies as "puff balls" at the bottom of the BCB, or as pellicle formation at the liquid-air interface, and gas production [7]. Automated systems outperform manual systems in terms of time-to-detection (TTD) and growth detection [7,[11][12][13][14][15][16], but they are expensive, require regular maintenance, and are not adapted to the environmental conditions commonly seen in low-resource settings (LRS) [17]. Therefore, many LRS laboratories still resort to manual blood culture systems.…”
Section: Introductionmentioning
confidence: 99%